Patient Characteristics and Treatment Patterns in European Pediatric Patients with Psoriasis: A Real-World, Cross-Sectional Study - Sticherling, Michael; Mcpherson, Tess; Laguna, Raul De Lucas; Costanzo, Antonio; Reed, Catherine; Artime, Esther; Robert, Camille; Lucas, James; Schuster, Christopher; Mahe, Emmanuel (Dermatology and Therapy, 2022)
Introduction This study evaluated patient characteristics and treatment patterns according to weight in pediatric patients with psoriasis in a real-world setting. Methods Primary care and specialist physicians treating pediatric patients with psoriasis aged 6-17 years in five European countries were surveyed in the 2019-2020 Adelphi Real World Pediatric Psoriasis Disease Specific Programme. At least two patients with current or previous biologic use were included per physician. Patient characteristics and treatment patterns were analyzed overall and for patients weighing 25-50 kg or more than 50 kg. Results Data from 772 patients weighing 25-50 kg and 1147 weighing more than 50 kg were analyzed. Median age at diagnosis was significantly less in lighter than heavier patients (10.0 vs. 14.0 years; p < 0.001), as was median disease duration (2.2 vs. 3.0 years; p < 0.001). Topical treatments were prescribed in 59.0% of patients overall (70.3% of lighter and 51.4% of heavier patients; p < 0.001), and were used to treat mild rather than moderate-to-severe psoriasis. Conventional systemic use was low (10.8% of patients overall) and predominantly for moderate-to-severe psoriasis. In this biologic-enriched sample, most biologics (78.2%) were prescribed in older (> 13 years) patients. Biologic use increased with line of therapy (6.6% of first-line, 18.0% of second-line, 33.7% of third-line, 44.7% of fourth-line treatments). Conclusion Biologics are predominantly prescribed in older (> 13 years) and heavier (> 50 kg) patients, with little first- or second-line use. The low use of biologics in European pediatric patients with psoriasis may represent an unmet treatment need, as topical or conventional systemic agents remain the main treatment option for moderate or severe psoriasis in these patients through the treatment pathway.
CRIS-Team WoS Importer:2022-07-22